Multidimensional Stigma and Social Support Networks Among Adolescents with Unintended Pregnancy in Makassar, Indonesia - Ruqaiyah Ruqaiyah (International Forum of Researchers and Lecturers, 2026)
This study examines the stigma and patterns of social support in adolescents with unplanned pregnancies in Makassar in the context of the Bugis-Makassar culture that upholds the values of siri' (honor and shame). Teen pregnancy is understood as an experience influenced by the confluence of traditional values, religious morality, and modern social demands. This study used an Interpretative Phenomenological Analysis (IPA) approach on 17 adolescent girls aged 15–19 years who experienced unplanned pregnancies in June–November 2023. Data were obtained through in-depth semi-structured interviews, recorded, verbatim transcribed, and analyzed using a six-stage science process with a focus on the experience of stigma and social support. Two main themes emerged: Living Under the Shadow of Siri': Multidimensional Stigma and Navigating Social Support in the Context of Shame. Participants experienced widespread stigma in a variety of contexts, including family (serial violations and family shame), society (moral judgments and gossip), health services (discrimination of health workers), and educational environments (bullying and exclusion). Stigma is also internalized in the form of guilt and negative identity, and is especially severe in adolescents with economic limitations. Efforts to seek support are often hampered by concerns about stigma, so adolescents engage in selective disclosure and rely more on peers. Grandma is often the most accepting source of family support. These findings underscore the need for multilevel interventions that reduce community stigma, strengthen friendly and confidential health services, and develop culturally sensitive peer support networks.